Posibilities for use of whole genome sequencing (WGS) for the analysis of Streptococcus pneumoniae isolates - Vohrnová, S; Kozáková, J (Epidemiologie, mikrobiologie, imunologie, 2024)
Streptococcus pneumoniae (pneumococcus) is a Gram-positive coccus causing both non-invasive and invasive infectious diseases. Pneumococcal diseases are vaccine preventable. Invasive pneumococcal diseases (IPD) meeting the international case definition are reported nationally and internationally and are subject to surveillance programmes in many countries, including the Czech Republic. An important part of IPD surveillance is the monitoring of causative serotypes and their frequency over time and in relation to ongoing vaccination programmes. In the world and in the Czech Republic, whole genome sequencing (WGS) is increasingly used for pneumococci, which allows for serotyping from sequencing data, precise analysis of their genetic relationships, and the study of genes present in their genome. Whole-genome sequencing enables the generation of reliable and internationally comparable data that can be easily shared. Sequencing data are analysed using bioinformatics tools that require knowledge in the field of natural sciences with an emphasis on genetics and expertise in bioinformatics. This publication presents some options for pneumococcal analysis, i.e., serotyping, multilocus sequence typing (MLST), ribosomal MLST (rMLST), core genome MLST (cgMLST), whole genome MLST (wgMLST), single nucleotide polymorphism (SNP) analysis, assignment to Global Pneumococcal Sequence Cluster (GPSC), and identification of virulence genes and antibiotic resistance genes. The WGS strategies and applications for Europe and WGS implementation in practice are presented. WGS analysis of pneumococci allows for improved IPD surveillance, thanks to molecular serotyping, more detailed typing, generation of internationally comparable data, and improved evaluation of the effectiveness of vaccination programmes.